PEMBEKALAN MENGENAI PEMBUATAN JURNAL UMUM PERUSAHAAN JASA DI SMK YP IPPI PETOJO SEBAGAI IMPLEMENTASI PROGRAM MBKM - Artina, Radinka Kaisya; Susanto, Liana (Jurnal Serina Abdimas, 2024)
Teaching assistance in educational units is one of the programs of the Merdeka Belajar Kampus Merdeka (MBKM) policy. This program provides freedom for students in organizing and designing their respective educational paths according to the interest and needs of each individual. This program is a form of Accounting carried out by Tarumanagara University students based on a plan that has been prepared by the by the School of SMK YP IPPI Petojo and supervisor from Tarumanagara University. In teaching assistance program, Tarumanagara University collaborates with SMK YP IPPI Petojo for 3 months starting from August 14th to October 27th 2023. This teaching assistance provides several objectives that have a positive influence on students and student who teach, for example to increase the knowledge of SMK YP IPPI Petojo student understanding and insight related to the application of knowledge in the world of education. The sources of this research are students of SMK YP IPPI Peotjo Class 10 and students who are carrying out teaching assistance majoring in accounting.